Outdoor Education Intervention for Increasing Student Assertive Attitude - Suhendra, Dede Iman; Satria, Teguh; Nur, Lutfi (Prodi PGSD Penjas FPOK UPI, 2020)
This research examined the impact of outdoor education on student assertive attitude in Laboratorium Percontohan UPI Elementary School, Tasikmalaya Campus, Indonesia. The problem gained by the researcher in the learning process was the negative behavior that the researcher aimed to study. The samples of the study were 32 students chosen through a purposive sampling technique. The experimental method was used in this study. The data were obtained through an Assertive Scale questionnaire. The researcher conducted an initial study with the result 0,662. The final score of the research was 0,504, showing that Outdoor Education had a significant impact on assertive attitude development. This finding shows that outdoor education can be an alternative for the teachers of Physical Education at elementary schools to implement moral and ethics learning as well as a learning variation. The further research is suggested to conduct a research related to other affective aspects, such as emotion and empathy. The outdoor education indirectly gives impacts on the student attitude and acts as a self-reminder.